Realistic Mathematics Education Toward Mathematical Communication Skills of Students using Hypothetical Learning Trajectory - Febriani, Winarti Dwi; Sidik, Geri Syahril (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
This research is motivated by the indispensability of learning that is able to bridge the students to understand a concept in mathematics. The difficulty of students to understanding the concept of fractions is still a problem in elementary school, so there is an assumption that learning mathematics is very difficult. Use of the learning trajectory or Hypothetical Learning Trajectory (HLT) became one of the alternatives for students to understand the concept of fractions in mathematics. The research is aimed to describe and analyze the existence of significant differences in improvement of students’ mathematical communication skills who learned and not learned used Realistic Mathematics Education (RME) with HLT. This research method is quasi-experimental with the pretest-postest nonequivalent design. The data collection instrument used was a mathematical communication skills test. The population of this research is all fourth grade students in one elementary school located in the district of Tawang, Tasikmalaya. The results of this research showed that based on data analysis N-gain scores, the value of Sig. (2-tailed) Equal Variances Assumed by 0,024 less than the significance level (α = 0.05), H0 is rejected and Ha accepted. Therefore, it can be concluded that the improvement of students' mathematical communication skills in the RME class (experimental class) is higher than the control class. Thus, there is a significant difference in improvement of students’ mathematical communication skills who learned and not learned used RME with HLT. The recommendation of this research is to conduct further research that can develop RMEbased Learning Trajectory in mathematics